2000
DOI: 10.1046/j.1537-2995.2000.40101198.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of HCV core antigen detection during the preseroconversion period

Abstract: HCV Ag testing permits the detection of an HCV infection about 1.5 months earlier than the HCV Ab screening tests and an average of only 2 days later than quantitative HCV RNA detection in individual specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 14 publications
8
95
0
Order By: Relevance
“…The first was developed by Tanaka et al (28) in 1995, and then Aoyagi et al (2) developed a new and 100-fold more sensitive test in 1999. In previously reported studies, HCV Ag was detected 1 day later than HCV RNA in patients undergoing seroconversion (5,6,20).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The first was developed by Tanaka et al (28) in 1995, and then Aoyagi et al (2) developed a new and 100-fold more sensitive test in 1999. In previously reported studies, HCV Ag was detected 1 day later than HCV RNA in patients undergoing seroconversion (5,6,20).…”
Section: Discussionmentioning
confidence: 76%
“…The anti-HCV test does not distinguish the individuals who have resolved HCV infection from the patients with active/ongoing HCV infection. As a consequence, anti-HCV assay results with values under the critical value used by EIA or CLIA need to be confirmed by an additional confirmatory test, such as the HCV RNA test, or with the preconfirmatory HCV Ag assay (5,10,14,17,25).…”
Section: Discussionmentioning
confidence: 99%
“…24 Courouse et al studied 135 serial specimens from 28 haemodialysis patients, and found that 88% of viraemic specimens contain HCVcAg. 26 One of our Devesa et al observed restricted antibody reactivity to Hepatitis C Virus synthetic antigens in patients on haemodialysis. 27 In the RIBA strip NS3 and NS5 antigen bands are recombinant proteins and the core and NS4 bands are of synthetic antigens.This could be one of the reasons for greater antibody response towards NS3 antigen among our haemodialysis patients.…”
Section: Discussionmentioning
confidence: 88%
“…False negative anti-HCV EIA results may occur in HIV-infected persons with advanced immune suppression (CD4 < 100/mm 3 ) and true negative EIA are common in the setting of acute HCV infection ( < 12 weeks following acquisition) prior to seroconversion [20][21]. If serologic test results are negative and HCV infection is suspected due to elevated liver enzyme levels or risk factors such as intravenous drug usage or high-risk sex, HCV RNA testing should be performed.…”
Section: Discussionmentioning
confidence: 99%